Navigating the new world of coral reef interventions in a time of climate change - Richards, Zoe (2018)
Over the last century, marine ecosystems have been profoundly impacted by human-induced global climate change. In locations where long-term datasets exist, stark changes in ecosystem compositions have been documented. Coral reef ecosystems are particularly susceptible to climate-induced changes because prolonged elevation of sea temperatures exerts tremendous stress on reef-building corals, leading to coral bleaching and, in some cases, large-scale mortality. For example, up to 90 per cent of corals growing on the northern Great Barrier Reef bleached in the 2016 coral bleaching event and approximately one quarter of these corals have subsequently died.